2016
DOI: 10.1002/fld.4294
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence modelling and role of compressibility on oil spilling from a damaged double hull tank

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository link AbstractThe viscosity plays an important role and a multi-phase solver is necessary to numerically simulate the oil spilling from a damaged double hull tank (DHT). However, it is uncertain whether turbulence modelling is necessary, which turbulence model is suitable; and what the role of compressibility of the fluids is. This paper presents experimental and numerical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The previous numerical works (e.g. Yang et al, 2017) have confirmed that such assumption is acceptable in the numerical practices.…”
Section: Interface Tracking and Transportmentioning
confidence: 62%
See 2 more Smart Citations
“…The previous numerical works (e.g. Yang et al, 2017) have confirmed that such assumption is acceptable in the numerical practices.…”
Section: Interface Tracking and Transportmentioning
confidence: 62%
“…In order to reveal the hydrodynamic feature of the oil leakage process, which has been confirmed in the above-mentioned experimental studies, the computational fluid dynamics (CFD) has also been attempted (e.g. Chang III and Lin, 1994;Cheng and Gomes, 2010;Tavakoli et al, 2011Tavakoli et al, , 2012Yang et al, 2014Yang et al, , 2016Yang et al, , 2017. Similar to the experimental studies, the majority of the numerical work did not take into account of the effects of the tank motion on the oil leakage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation